Postvaccination anti-S IgG levels predict anti-SARS-CoV-2 neutralising activity over 24 weeks in patients with RA. Issue 2 (26th October 2022) - Schmiedeberg, Kristin; Abela, Irene A; Pikor, Natalia Barbara; Vuilleumier, Nicolas; Schwarzmueller, Magdalena; Epp, Selina; Pagano, Sabrina; Grabherr, Sarah; Patterson, Angelica Brooke; Nussberger, Madalina; Trkola, Alexandra; Ludewig, Burkhard; et al.
Abstract : Objectives: To correlate immune responses following a two-dose regimen of mRNA anti-SARS-CoV-2 vaccines in patients with rheumatoid arthritis (RA) to the development of a potent neutralising antiviral activity. Methods: The RECOVER study was a prospective, monocentric study including patients with RA and healthy controls (HCs). Assessments were performed before, and 3, 6, 12 and 24 weeks, after the first vaccine dose, respectively, and included IgG, IgA and IgM responses (against receptor binding domain, S1, S2, N), IFN-γ ELISpots as well as neutralisation assays. Results: In patients with RA, IgG responses developed slower with lower peak titres compared with HC. Potent neutralising activity assessed by a SARS-CoV-2 pseudovirus neutralisation assay after 12 weeks was observed in all 21 HCs, and in 60.3% of 73 patients with RA. A significant correlation between peak anti-S IgG levels 2 weeks after the second vaccine dose and potent neutralising activity against SARS-CoV-2 was observed at weeks 12 and 24. The analysis of IgG, IgA and IgM isotype responses to different viral proteins demonstrated a delay in IgG but not in IgA and IgM responses. T cell responses were comparable in HC and patients with RA but declined earlier in patients with RA. Conclusion: In patients with RA, vaccine-induced IgG antibody levels were diminished, while IgA and IgM responses persisted, indicating a delayed isotype switch. Anti-S IgG levels 2 weeks after the second vaccine dose correlate with the development of a potent neutralising activity after 12 and 24 weeks and may allow to identify patients who might benefit from additional vaccine doses or prophylactic regimen.